2005
DOI: 10.1128/jvi.79.4.2108-2114.2005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Movement Protein of Rice Yellow Stunt Rhabdovirus

Abstract: Rice yellow stunt virus (RYSV) is a member of the plantinfecting Nucleorhabdovirus genus of the Rhabdoviridae family (35). RYSV has a nonsegmented, negative-sense single-stranded RNA genome which contains a 5Ј trailer, a 3Ј leader, and seven open reading frames (ORFs) in the order

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 38 publications
1
52
0
3
Order By: Relevance
“…The P:P3 interaction is characterized by the re-localization of some P3 from the cell periphery to the nucleus. GST pull-down assays showed that RYSV P3 specifically binds to cognate N protein, indicating its involvement in cell-to-cell movement (Huang et al, 2005). On the other hand, the putative movement protein of PYDV was shown to interact with cognate M and G proteins (Bandyopadhyay et al, 2010), whereas SYNV sc4 interacts with the G protein (Min et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…The P:P3 interaction is characterized by the re-localization of some P3 from the cell periphery to the nucleus. GST pull-down assays showed that RYSV P3 specifically binds to cognate N protein, indicating its involvement in cell-to-cell movement (Huang et al, 2005). On the other hand, the putative movement protein of PYDV was shown to interact with cognate M and G proteins (Bandyopadhyay et al, 2010), whereas SYNV sc4 interacts with the G protein (Min et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…The extra gene that we have named Y is in a similar genomic context to the sc4 gene of SYNV, and P3 of RYSV, both of which have been implicated in cell-to-cell movement in these viruses (Huang et al, 2005; Melcher, 2000). The subcellular localization pattern of PYDV-Y is on the periphery of the cells and in this respect is highly similar to that of sc4 (Goodin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For example, MPs of Rice dwarf virus and Rice yellow stunt virus were used to complement PVX mutant movement in N. benthamiana plants (11,18). Even more interesting, Flock House virus, an insect virus, can spread in N. benthamiana plants expressing MP of TMV or Red clover necrotic mosaic virus (7).…”
Section: Discussionmentioning
confidence: 99%
“…Construct pBI-P25, expressing the PVX p25 protein, was provided by R. X. Fang (Institute of Microbiology, Chinese Academy of Sciences) (11). Six ORFs of RSV (i.e., NS2, NSvc2, NS3, NCP, NSvc4, and SP) were amplified individually from total RNA extracted from RSV-infected rice tissues collected from a rice field in the Jiangsu province using Pfu DNA polymerase and specific primer pairs (NS2-F/NS2-R for NS2, NSvc2-F/NSvc2-R for NSvc2, NS3-F/NS3-R for NS3, NCP-F/NCP-R for NCP, NSvc4-F/NSvc4-R for NSvc4, and SP-F/SP-R for SP) ( Table 1).…”
Section: Constructs and Procedures For Complementation Experimentsmentioning
confidence: 99%